DEFAULT AND NEGOTIABLE OBLIGATIONS: LEGAL AND SOCIOLOGICAL ANALYSIS OF IMPLICATIONS AND STRATEGIES FOR CONTRACTUAL BALANCE (CIPEEX, 2025)
The Law of Obligations encompasses rights of a patrimonial nature, with negotiable obligations arising from agreements between parties. This paper aims to describe the main negotiable obligations in daily life and analyze the legal ramifications of default, discussing effective strategies for creditors and debtors. The analysis considers norms present in the Civil Code, Code of Civil Procedure, Penal Code, and Consumer Defense Code. The methodology adopts a bibliographic review, analysis of recent jurisprudence from the Court of Justice of Goiás (2021-2024), and concepts from legal sociology, based on authors such as Durkheim and other renowned scholars, to provide a broader understanding of the impact of default on unavailable rights, such as personality and moral rights. Finally, the article suggests prevention and resolution practices for those involved.
Keywords: Default; Negotiable obligations; Debtor; Creditor; Legal consequences.